Research Projects development prospective in EU GREEN Alliance Concortium - Volovyk, Iryna Anatoliivna; Воловик, Ірина Анатоліївна; Tkalich, Yurii Igorevych; Ткаліч, Юрій Ігоревич (Center for Ukrainian and European Scientific Cooperation, 2023)
Global, national, and professional alliances of the Universities have been making impact for education, innovation, culture, and social development of their members, influencing, and driving the positive changes in their field of science, communities, countries. Глобальні, національні та професійні альянси університетів впливають на освіту, інновації, культуру та соціальний розвиток їхніх членів, впливаючи та стимулюючи позитивні зміни у своїй галузі науки, спільнотах, країнах.
Перспектива розвитку дослідницьких проектів у консорціумі EU GREEN Alliance
Keywords: Global, national, and professional alliances of the Universities; глобальні, національні та професійні альянси університетів; impact on education, innovation, culture and social development; вплив на освіту, інновації, культуру та соціальний розвиток